Characterization of non-volatile and volatile flavor profiles of Coregonus peled meat cooked by different methods - Wengang Jin; Xinru Fan; Caiyan Jiang; Yang Liu; Kaiyue Zhu; Xiaoqing Miao; Pengfei Jiang (Food Chemistry: X, 2023)
This study investigated the effects of different cooking methods on non-volatile flavor (free amino acids, 5′-nucleotides, and organic acids, etc.) of Coregonus peled meat. The volatile flavor characteristics were also analyzed by electric nose and gas chromatography-ion migration spectrometry (GC-IMS). The results indicated that the content of flavor substances in C. peled meat varied significantly. The electronic tongue results indicated that the richness and umami aftertaste of roasting were significantly greater. The content of sweet free amino acids, 5′-nucleotides, and organic acids was also higher in roasting group. Electronic nose principal component analysis can distinguish C. peled meat cooked (the first two components accounted for 98.50% and 0.97%, respectively). A total of 36 volatile flavor compounds were identified among different groups, including 16 aldehydes, 7 olefine aldehydes, 6 alcohols, 4 ketones, and 3 furans. In general, roasting was recommended and gave more flavor substances in C. peled meat.